Pengaruh Budaya Organsiasi, Beban Kerja, dan Lingkungan Kerja Terhadap Kinerja Karyawan pada PT. Pos Indonesia Cabang Kediri - Desita Rahmah Hidayah; Indah Yuni Astuti; Angga Permana Mahaputa (Jurnal Inovasi Manajemen, Kewirausahaan, Bisnis dan Digital, 2026)
This study aims to analyze the effects of organizational culture, workload, and work environment on employee performance at PT Pos Indonesia Kediri Branch. A quantitative approach was employed, with data collected through questionnaires distributed to employees. The data were analyzed using linear regression to examine the relationships between the independent variables and employee performance. The results indicate that organizational culture has a positive and significant effect on employee performance, with a regression coefficient of 1.200 and a significance value of 0.035 (<0.05). Workload also has a positive and significant effect on employee performance, with a regression coefficient of 0.210 and a significance value of 0.000 (<0.05). In addition, the work environment positively and significantly influences employee performance, with a regression coefficient of 0.283 and a significance value of 0.041 (<0.05). These findings suggest that strengthening organizational culture, managing workload effectively, and creating a conducive work environment can improve employee performance.